Proteome changes of plasma-derived extracellular vesicles in patients with myelodysplastic syndrome - Pecankova, Klara; Pecherkova, Pavla; Gasova, Zdenka; Sovova, Zofie; Riedel, Tomas; Jäger, Eliézer; Cermak, Jaroslav; Majek, Pavel (PloS one, 2022)
BACKGROUND: Extracellular vesicles are released into body fluids from the majority of, if not all, cell types. Because their secretion and specific cargo (e.g., proteins) varies according to pathology, extracellular vesicles may prove a rich source of biomarkers. However, their biological and pathophysiological functions are poorly understood in hematological malignancies. OBJECTIVE: Here, we investigated proteome changes in the exosome-rich fraction of the plasma of myelodysplastic syndrome patients and healthy donors. METHODS: Exosome-rich fraction of the plasma was isolated using ExoQuick™: proteomes were compared and statistically processed; proteins were identified by nanoLC-MS/MS and verified using the ExoCarta and QuickGO databases. Mann-Whitney and Spearman analyses were used to statistically analyze the data. 2D western blot was used to monitor clusterin proteoforms. RESULTS: Statistical analyses of the data highlighted clusterin alterations as the most significant. 2D western blot showed that the clusterin changes were caused by posttranslational modifications. Moreover, there was a notable increase in the clusterin proteoform in the exosome-rich fraction of plasma of patients with more severe myelodysplastic syndrome; this corresponded with a simultaneous decrease in their plasma. CONCLUSIONS: This specific clusterin proteoform seems to be a promising biomarker for myelodysplastic syndrome progression.
Keywords: senioři; proteomika; Male; Myelodysplastic Syndromes; mužské pohlaví; studie případů a kontrol; myelodysplastické syndromy; Extracellular Vesicles; Proteomics; ženské pohlaví; Proteome; Humans; Tandem Mass Spectrometry; biologické markery; chromatografie kapalinová; extracelulární vezikuly; tandemová hmotnostní spektrometrie; proteom; Biomarkers; Chromatography, Liquid; Female; Aged; lidé; Case-Control Studies